2-Naphthylmethyl N-(3-pyridylmethylene) hydrazinecarbodithioate. - How, Fiona N.-F.; Watkin, David J.; Crouse, Karen Anne; Mohamed Tahir, Mohamed Ibrahim (International Union of Crystallography, 2007)
The title molecule, C18H15N3S2, is a trans-cis conformer. The thione S atom is in a trans configuration with respect to the pyridine ring but adopts a cis configuration with respect to the napthylmethyl substituent. In the crystal structure, molecules are linked by intermolecular N-H...N hydrogen bonds via[alpha]-N donor atoms and pyridyl N acceptor atoms into one-dimensional chains along the a axis. In addition, pairs of inversion-related dithiocarbazate groups and the attached pyridine groups are arranged with an interplanar distance 3.30 Å, leading to [pi]-[pi] stacking interactions. The crystal used for the structure determination was twinned.